2014
DOI: 10.32674/jis.v4i4.450
|View full text |Cite
|
Sign up to set email alerts
|

East Asian International Students and Psychological Well-Being: A Systematic Review

Abstract: The present article reports a systematic review of the studies related to psychological well-being among East Asian international students. A total of 18 quantitative studies published in peer-reviewed journals from 2000 to 2011 were reviewed. Our review revealed three major results: (1) a majority of researchers (n=13, 72.2%) tend to choose Chinese international students as a representative of East Asian and Asian international students in their studies; (2) studies on psychological well-being of East Asian i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 49 publications
1
25
1
3
Order By: Relevance
“…Acculturative stress represents a growing threat to the health of many first-year international students as they seek knowledge in an unfamiliar cultural environment (Li et al, 2014). A study conducted by Russsell et al (2010) involving 900 international students attending colleges in the US showed that 41% of these students experienced substantial levels of stress in their first year.…”
Section: Acculturative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Acculturative stress represents a growing threat to the health of many first-year international students as they seek knowledge in an unfamiliar cultural environment (Li et al, 2014). A study conducted by Russsell et al (2010) involving 900 international students attending colleges in the US showed that 41% of these students experienced substantial levels of stress in their first year.…”
Section: Acculturative Stressmentioning
confidence: 99%
“…International students, both graduate and undergraduate, experience a great amount of stress and anxiety when they enroll in a university outside of their country of origin (Li et al, 2014;Russel, 2010). Acculturative stress -as well as adapting to a new culture, language, and customs -plays a significant role in the students' levels of anxiety.…”
Section: Relational Skillsmentioning
confidence: 99%
“…International students can be categorized as sojourners, or individuals who stay in the host country for a short period of time to attain a particular goal and then return to their home country (Li, Wang, & Xiao, 2019). They are immersed in an educational environment where they have a unique set of experiences within a specialized population.…”
Section: Introductionmentioning
confidence: 99%
“…Problems with a foreign language (e.g., American English), lack of understanding of American culture, and immigration-related issues are just a few examples of the many challenges that students' experience when studying in the U.S. (Smith & Khawaja, 2011;Wu et al, 2015). These challenges are particularly troublesome for East Asian students, the largest international student group studying in the U.S., considering the large cultural gap between East Asia and the U.S. (Li et al, 2019). Compared to students from other parts of the world such as Europe and South Asia, East Asian international students often experience communication difficulties and perceived prejudice, making them less likely to seek help for their respective challenges (Frey & Roysircar, 2006;Jones & Kim, 2013).…”
mentioning
confidence: 99%